Fishes in Warming Waters, the Gill-Oxygen Limitation Theory and the Debate Around Mechanistic Growth Models - Johannes Müller; Daniel Pauly (Fishes)
Mechanistic explanations of the impact of climate change on fish growth are currently under debate. However, critical assessments of even the most prominent theories are not always based on accurate interpretations of their underlying mechanistic models. This contribution addresses some of the major misunderstandings still causing the Gill-Oxygen Limitation Theory (GOLT) from being examined based on its actual structuring elements and assumptions, rather than erroneous perceptions. As we argue, recent critiques of the GOLT are based on implausible interpretations of respirometry data that are invoked to distinguish maintenance costs and overhead costs of growth. Discussing the current state of the debate, we emphasize the fact that fasting young and, thus, growing fish for short periods of time is not sufficient to suppress energy (i.e., oxygen) allocation to growth. In the process of dealing with these issues, several cases of apparent ‘counter-evidence’ are discussed. Highlighting the need to base critical discussions and examinations of the GOLT on its actual predictions, we recommend that testing the theory should focus on broad reviews or meta-analyses, e.g., on datasets of gill surface area and the relationship of these data to growth performance under different temperature regimes.